Possible plasmonic acceleration of LED modulation for Li-Fi applications - Guzatov, D. V. (2020)
Emerging LED-based wireless visible light communication (Li-Fi) needs faster LED response to secure desirable modulation rates. Decay rate of an emitter can be enhanced by plasmonics, typically by an expense of efficiency loss because of non-radiative energy transfer. In this paper, metal-enhanced radiative and non-radiative decay rates are shown to be reasonably balanced to get with Ag nanoparticles nearly 100-fold enhancement of the decay rate for a blue LED without loss in overall efficacy. Additionally, gain in intensity occurs for intrinsic quantum yield Q0 < 1. With silver, rate enhancement can be performed through the whole visible. For color-converting phosphors, local field enhancement along with decay rate effects enable 30-fold rate enhancement with gain in efficacy. Since plasmonics always enhances decay rate, it can diminish Auger processes thus extending LED operation currents without efficiency droop. For quantum dot phosphors, plasmonic diminishing of Auger processes will improve photostability.